2016
DOI: 10.1108/jes-02-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Financial integration, global liquidity and global macroeconomic linkages

Abstract: Purpose – The purpose of this paper is to analyse the effect of financial integration on several macroeconomic variables from a global perspective. Design/methodology/approach – The authors apply a cointegrated vector autoregression model using quarterly data for 1980-2009. Analysing the interactions of globally aggregated measures capturing cross-border financial transactions, monetary liquidity, output, consumer and commodity prices, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…Of course, the dominance of sector 7 is also validated by the fact that this sector, based on the respective GIRFs, is not statistically significantly affected by unexpected/unanticipated unit shocks in the rest of the sectors, while a shock in the dominant sector seems to have a statistically significant effect on the majority of the US sectors. This is, in general terms, consistent with the work of Belke and Keil (2016), who argue that financial integration per se and therefore the financial sector in general affects the overall output of the economy.…”
Section: Discussionsupporting
confidence: 90%
“…Of course, the dominance of sector 7 is also validated by the fact that this sector, based on the respective GIRFs, is not statistically significantly affected by unexpected/unanticipated unit shocks in the rest of the sectors, while a shock in the dominant sector seems to have a statistically significant effect on the majority of the US sectors. This is, in general terms, consistent with the work of Belke and Keil (2016), who argue that financial integration per se and therefore the financial sector in general affects the overall output of the economy.…”
Section: Discussionsupporting
confidence: 90%
“…Economic policymakers will be able to predict the behaviour of the JUJBR selected macroeconomic variable when any change is observed in liquidity and vice versa. Belke and Keil (2016) found that financial integration drives the prices of the commodity. They also find that the break between financial flow and dynamics of the commodity prices is corrected by the global liquidity managed by central bank.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we follow Belke and Keil (2016), Giese and Tuxen (2007) and Beyer et al (2001) to construct monetary aggregates at regional and global levels. This procedure of aggregation involves the conversion of nominal GDP of all countries into a common currency using purchasing power parity (PPP) exchange rates.…”
Section: Gdp-weighted Growth Rates Methodsmentioning
confidence: 99%
“…where, g it is the growth rate of broad money of country i in time t and G t is the aggregate growth rate in time t. Some studies use year specific weights at this stage of aggregation because the data on GDP is generally available in annual frequency (Belke and Keil 2016;Belke et al 2014;Baks and Kramer 1999). We also use year specific weights at this step of aggregation.…”
Section: Gdp-weighted Growth Rates Methodsmentioning
confidence: 99%
See 1 more Smart Citation